Decomposition of Organic Compounds by UV/TiO2 System - Won1, Hui-Jun; Jung1, Chong-Hun; Jung1, Cheol-Jin; Moon1, Jei-Kwon; Lee1, Ki-Won; Chung2, Won-Yang (Asian Journal of Chemistry, 2011)
The photodecomposition characteristics of EDTA, oxalic acid and ascorbic acid were investigated. Adsorption tests of EDTA, oxalic acid and ascorbic acid on a TiO2 surface were also performed. For a one component system, the order of decomposition rate chosen from a COD measurement was oxalic acid > EDTA > ascorbic acid. For a two component system, the decomposition rate of a mixed EDTA + oxalic acid solution was fastest among the test solutions. Decomposition of an ascorbic acid + oxalic acid solution was more difficult than the decomposition of an EDTA + ascorbic acid solution. This can be explained by the adsorption characteristics of organic compounds onto the TiO2 surface. For a three component system, which was a mixed solution of EDTA, oxalic acid and ascorbic acid, more than 95 % of the total organic carbon was decomposed during a 16 h period. The reaction time was reduced due to the successive application of Fenton process and photodecomposition process